Psychometric Properties of the Lactation Assessment and Comprehensive Intervention Tool (LAT) - Julie Grady; Anna Blair; Kajsa Brimdyr; Karin Cadwell (Nursing Reports)
Background: Despite the short- and long-term acknowledged benefits of breastfeeding for mothers and their infants, worldwide rates trail behind international goals. Prior research confirms that breastfeeding is a nurse sensitive indicator and that problems with latching the baby and painful breastfeeding rank high among the reasons given for not continuing to breastfeed. The Lactation Assessment Tool (LATTM) was previously evaluated in a study conducted in Latvia by nurse midwives. Use of the LAT to assess breastfeeding and suggesting corrective interventions were shown to decrease pain and promote healing in traumatized nipples. The inter-rater reliability for that study was by test/re-test amongst participating researcher midwives. The aim of the current study is to expand the understanding of LAT inter-rater reliability to include novice and expert assessors. Methods: A convenience sample of twenty participants, including both novices (nine nursing students) and 11 self-identified experts, assessed four videos of breastfeeding dyads using the assessment tool, the LAT. Novice participants received a 2 h training session before final tool assessment. Each video was viewed three times, with a 3 min pause between viewings. All elements of the LAT that could be visually evaluated were included, with each element appearing in at least two of the videos. Results: Acceptable internal consistency of the LAT tool was found, with Cronbach’s alpha measuring 0.799, 0.740, 0.756 and 0.735 for each video, respectively. The reliability of the novice assessors improved over the course of the four videos, from 0.484 and 0.610 to 0.714 and 0.711. All of the experts had Cronbach’s alpha numbers that were acceptable, ranging from 0.769 to 1.00. Conclusions: Results indicate that experts perform much better using the tool than trained novices. However, the subsequent use of the tool resulted in the last two video assessments having an acceptable measure for the trained novice group. The LAT is a reliable tool for trained novices and experts to assess breastfeeding positioning and latch.